Materiais biopoliméricos multicamadas produzidos por casting contínuo e deposição por sopro em solução - Franco, Giuliana Thalina (Universidade Federal de São Carlos, 2024)
In line with the growing demand for sustainable strategies to minimize the environmental impacts caused by plastics, natural and biodegradable polymers emerge as substitutes, albeit partially, for petrochemical polymers that are non-biodegradable. In this work, we pioneered the development of multilayer biopolymeric materials using contemporary processing techniques as continuous solvent evaporation (or continuous casting) and solution blow deposition (SBD). The work focused on multistructuring different biopolymers to promote a compatible system with their properties combined in a system containing three layers.To achieve this, bilayer films were initially produced by consecutive lamination steps of carboxymethylcellulose (CMC) as a support layer and casein layer, which exhibits good barrier properties. Additionally, a hydrophobic layer of zein was sprayed on the bilayer film to reduce the material's susceptibility to humidity. The key concept of this system is the interfacial compatibility between biopolymeric layers, which ensures a synergic relationship between the components. Incorporating tannic acid (TA) and 1,1,4,4-butanetetracarboxylic acid (BTCA) into the CMC layer, along with their respective proportions, was investigated to promote interfacial adhesion of the bilayer. The appropriate rheological aspects for the zein deposition on the bistructured films and its influence on the interaction with water were studied. The multilayer materials were extensively characterized according to their generic characteristics (mechanical, barrier, thermal, morphological, and structural), and the interfacial adhesion energies were quantified using atomic force microscopy (AFM). This research showed that multilayer films are a strategy for combining proteins and polysaccharides in a material with an interface that covers its entire two-dimensional extension. Also, the study allowed for the understanding of the aspects that influence the compatibility of biopolymers and the forces responsible for interfacial interactions.
Production of multilayer biopolymeric materials by continuous casting and solution blow deposition
Keywords: Biopolímeros; Materiais multicamadas; Deposição por sopro em solução; Casting contínuo; Forças de adesão; Microscopia de força atômica; Biopolymers; Multilayer materials; Solution blow deposition; Continuous casting; Adhesion forces; Atomic force microscopy; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA